2019
DOI: 10.1136/ejhpharm-2019-002016
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis induced by ixekizumab: a case report

Abstract: A possible case of ulcerative colitis (UC) developed during treatment with ixekizumab is reported. Ixekizumab is a human monoclonal antibody approved for chronic plaque psoriasis that works by blocking interleukin-17 (IL-17). Cytoquines, such as IL-17, may be involved in the pathophysiology of psoriasis and inflammatory bowel diseases. We describe the case of a 76-year-old woman who presented with an episode of acute self-limited colitis after receiving ten doses of ixekizumab. It was resolved after treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…A total of 29 studies were identified in the published literature, including 25 case reports ( Ehrlich et al, 2018 ; Grimaux et al, 2018 ; Paul et al, 2018 ; Wang et al, 2018 ; Achufusi et al, 2019 ; Grossberg, 2019 ; Haidari et al, 2019 ; Johnston and Veettil, 2019 ; Philipose et al, 2019 ; Rodriguez et al, 2019 ; Shimizu et al, 2019 ; Smith et al, 2019 ; Darch et al, 2020 ; Fieldhouse et al, 2020 ; Marin et al, 2020 ; Merino Gallego et al, 2020 ; Nazarian et al, 2020 ; Ali et al, 2021 ; Mu et al, 2021 ; Obeidat and Murakami, 2021 ; Ma et al, 2022 ; Sykaras et al, 2022 ; Kukol et al, 2019 ; Nallapeta et al, 2019 ; Sethi et al, 2019 ) and 4 case series ( Fobelo et al, 2018 ; Shukla et al, 2018 ; Vernero et al, 2019 ; Lee et al, 2020 ); a total of 34 cases raised evidence of IBD occurrence during therapy with SEC (27 cases, 79.4%) and IXE (7 cases, 20.6%). Characteristics of the included cases are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 studies were identified in the published literature, including 25 case reports ( Ehrlich et al, 2018 ; Grimaux et al, 2018 ; Paul et al, 2018 ; Wang et al, 2018 ; Achufusi et al, 2019 ; Grossberg, 2019 ; Haidari et al, 2019 ; Johnston and Veettil, 2019 ; Philipose et al, 2019 ; Rodriguez et al, 2019 ; Shimizu et al, 2019 ; Smith et al, 2019 ; Darch et al, 2020 ; Fieldhouse et al, 2020 ; Marin et al, 2020 ; Merino Gallego et al, 2020 ; Nazarian et al, 2020 ; Ali et al, 2021 ; Mu et al, 2021 ; Obeidat and Murakami, 2021 ; Ma et al, 2022 ; Sykaras et al, 2022 ; Kukol et al, 2019 ; Nallapeta et al, 2019 ; Sethi et al, 2019 ) and 4 case series ( Fobelo et al, 2018 ; Shukla et al, 2018 ; Vernero et al, 2019 ; Lee et al, 2020 ); a total of 34 cases raised evidence of IBD occurrence during therapy with SEC (27 cases, 79.4%) and IXE (7 cases, 20.6%). Characteristics of the included cases are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Marin M et al reported the case of a case of a 76-year-old Spanish woman who presented with acute self-limited colitis after receiving ten doses of ixekizumab for her pre-existing, long-standing chronic plaque psoriasis [ 65 ]. She had previously been treated with methotrexate 20 mg, acitretin 25 mg, both of them being withdrawn due to intolerance, and adalimumab 40 mg subcutaneously for two years [ 65 ]. The patient was then switched to ustekinumab 45 mg every 12 weeks due to loss of therapeutic response to the TNF-alpha inhibitor [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…She had previously been treated with methotrexate 20 mg, acitretin 25 mg, both of them being withdrawn due to intolerance, and adalimumab 40 mg subcutaneously for two years [ 65 ]. The patient was then switched to ustekinumab 45 mg every 12 weeks due to loss of therapeutic response to the TNF-alpha inhibitor [ 65 ]. Nevertheless, after five doses of ustekinumab, the patient developed bullous pemphigoid, possibly in the context of biologic therapy with the IL-12/23 inhibitor [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case report also presented a patient with psoriasis who was treated with ixekizumab and after 12 weeks of the induction period developed diarrheal illness and rectal bleeding [117]. Marin et al reported a case of acute selflimited UC occurring in a patient treated with ixekizumab for psoriasis, and the colitis was quickly resolved after treatment withdrawal [118]. For patients with psoriasis and IBD, anti-IL-17 agents should be avoided.…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%